Intraosseous Mucoepidermoid Carcinoma of the Mandible: A Case Report with Three-Year Follow-Up - Zamani, Toktam; Mohtasham, Nooshin; Raeiszadeh Langarodi, Seyedeh Sara; Jannat Abadi, Ehsan (Asian Pacific Journal of Cancer Care, 2025)
Background: Mucoepidermoid carcinoma (MEC) is the most common malignant salivary gland tumor, but its intraosseous (central) presentation in the jaws is extremely rare and often mimics benign odontogenic lesions. Case: We describe a 37-year-old woman with swelling and dull pain in the left mandible. Clinical and radiographic evaluation, including cone-beam computed tomography (CBCT), revealed a destructive multilocular radiolucent lesion with cortical perforation. Treatment: An incisional biopsy confirmed the diagnosis of low-grade intraosseous MEC. The lesion was surgically excised, and mandibular reconstruction was performed using an autogenous fibular bone graft. Outcome: At a three-year follow-up, the patient showed complete recovery with no evidence of recurrence. This case underscores the importance of timely diagnosis, appropriate surgical management, and long-term follow-up in intraosseous salivary gland malignancies.